PENGARUH TEKANAN PENDUDUK DAN PENDAPATAN PETANI TERHADAP KONSERVASI LAHAN DAERAH ALIRAN SUNGAI WALIKAN HULU KABUPATEN KARANGANYAR TAHUN 2012 - Dwi Ningsih, Yuliana (Pendidikan Geografi, 2013)
ABSTRACTThe purposes of this research are to: (1) Know the population pressure. (2) Knowthe land productivity and income of farmers. (3) Know the condition of landconservation. (4) Know the effect of population pressure toward the land conservationand income of farmers toward the land conservationThis study used a qualitative descriptive method. The study was performed oneach unit of land, farmers sampling was taken by snow ball purposive sampling.The conclusions of this study were: (1) The polulation pressure varying that is,Wonorejo village has a highest population pressure, while Wonokeling village has amiddle population pressure. (2) Land productivity and income of farmers is varying, asfollows: (a) The area of land productivity research is varies, 7,57% low landproductivity, 79,85% middle land productivity, and 12,58% highland productivity, (b)The income farmers on the research is varies, 61,54% of low-income farmers, 38,06%middle-income farmers, and high-income farmers is only 0,40%. (3) The condition ofland conservation is varies, 49,80% low land conservation, 45,32% middle landconservation and 4,88% high land conservation. (4) Effect of population pressuretoward the land conservation and income of farmers toward the land conservation is:(a) Population pressure has no directly influence toward the land conservation, (b)Farmers with low income tend to conserve the land at the low level and high incomefarmers tend to conserve the land at the high level.Keywords: Population pressure, Income of farmers, Land conservation